HUBUNGAN STATUS PEKERJAAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS KAWANGKOAN - Timporok, Anggania G.A; Wowor, Pemsi M; Rompas, Sefti (JURNAL KEPERAWATAN, 2018)
Abstract : breast milk is the best food for the baby’s growth. Nutrient found in breast milk is very complete and very beneficial to the baby. ASI is Exclusive breast feeding to baby food and drinks without an escort which started since the new baby is born. Purpose:of this research is to know the relation of maternal employment status with exclusive breast feeding. Research methods: method using descriptive analytic with cross sectional study approach. The sample uses the total sampling method i.e. 72 mother while giving exclusive breast milk at work-area Clinics Kawangkoan. This research use questionnaire instruments and data analysis using Chi- Square test Results: based on Chi-square test results showed the existence of a relationship between the two variables with the value p = 0.000 less than Î± = 0.05. The conclusion: There is significant correlation between occupational status with the exclusive breastfeeding working area of Kawangkoan public health. Keyword: Occupational status, Exclusive breast feeding Abstrak : ASI merupakan makanan terbaik bagi tumbuh kembang bayi. Kandungan gizi yang terdapat dalam ASI sangat sempurna dan sangat bermanfaat bagi bayi. Asi eksklusif adalah pemberian ASI (air susu ibu) sedini mungkin setelah persalinan sampai bayi berumur 6 bulan. Tujuan penelitian ini untuk mengetahui hubungan status pekerjaan ibu dengan pemberian ASI eksklusif. Metode penelitian menggunakan metode deskriptif analitik dengan pendekatan cross sectional study. Sampel Penelitian ini menggunakan instrumen kuesioner dan analisa data menggunakan uji Chi-Square. Hasil penelitian berdasarkan uji Chi-square menunjukan hasil adanya hubungan antara kedua variabel dengan nilai p=0,000 kurang dari Î±=0,05. Kesimpulan dari penelitian ini adalah ada hubungan anatar status pekerjaan ibu dengan pemeberian ASI eksklusif di wilayah kerja Puskesmas Kawangkoan. Kata Kunci: Status Pekerjaan Ibu, ASI Eksklusif. Â